Knowledge Management Implementation, Innovation, and Organisational Performance: An Empirical Study in the Iraqi Mobile Telecommunications Sector - Al-hakim, Laith Ali Yousif (2012)
In today's Mobile Telecommunications Sector (MTS), Knowledge Management (KM) has become a lifeline. Even as the complexity of KM has increased due to a deficient comprehension of core requirements for successful implementation, a great need has developed for a better understanding of KM's role in affecting innovation and Organizational Performance (OP) in the MTS context. This need is particularly acute in developing countries such as Iraq. To address these requisites, an integrative theoretical framework was developed based on the perspectives of the Resource-Based View and Knowledge-Based View theories. The framework describes the relationships among core requirements of KM implementation (critical successes factors, strategies, and processes) and OP through the mediating role of innovation. To test this framework, a quantitative approach using the survey method was employed. Based on proportionate stratified random sampling, 300 questionnaires were distributed to mid-level managers in Iraqi MTS between March and June, 2011. Of these, 220 questionnaires were usable, resulting in a response rate of about 73.3%. The data were analysed using the structural equation model. The findings indicated that overall core requirements of KM implementation had a statistically significant and direct, positive effect on innovation. Both critical success factors and strategies of KM had a statistically significant, direct positive effect on OP. The direct relationship of KM processes with OP was positive, although not statistically significantly. Innovation had a positive, statistically significant effect on OP. More importantly, the findings indicated that overall core requirements of KM implementation had a positive, statistically significant effect on OP, through the partial mediating effect of innovation. These results offer theoretical, methodological, and practical contributions and will help academics and practitioners in KM field. Nonetheless, further studies are necessary both to confirm the findings and to incorporate additional variables that may influence results.